Spontaneous formation of structurally diverse membrane channel architectures from a single antimicrobial peptide - Wang, Yukun (Nature Publishing Group, 2016)
Many antimicrobial peptides (AMPs) selectively target and form pores in microbial membranes. However, the mechanisms of membrane targeting, pore formation and function remain elusive. Here we report an experimentally guided unbiased simulation methodology that yields the mechanism of spontaneous pore assembly for the AMP maculatin at atomic resolution. Rather than a single pore, maculatin forms an ensemble of structurally diverse temporarily functional low-oligomeric pores, which mimic integral membrane protein channels in structure. These pores continuously form and dissociate in the membrane. Membrane permeabilization is dominated by hexa-, hepta- and octamers, which conduct water, ions and small dyes. Pores form by consecutive addition of individual helices to a transmembrane helix or helix bundle, in contrast to current poration models. The diversity of the pore architectures—formed by a single sequence—may be a key feature in preventing bacterial resistance and could explain why sequence–function relationships in AMPs remain elusive.